Das fortdauernde Erbe der Sklaverei in der Karibik. Warum karibische Staaten Reparationen von Europa fordern - Rauhut, Claudia (Comparativ, 2021)
This article deals with current demands for reparations for slavery in the context of the agenda of the CARICOM Reparations Commission, a transregional alliance of civil society activists from predominantly Anglophone Caribbean states. Since 2013 they have been calling on European governments to take measures to combat the consequences of slavery and colonial rule in their former colonies. After a short introduction to the global historical and geostrategic significance of the Caribbean for an analysis of global inequalities based on the transatlantic slave trade and Caribbean plantation slavery, a historical contextualization of reparations demands follows. Based on my ethnological research in Jamaica, in which I conducted qualitative interviews with National Council for Reparations activists, I give an overview of their central arguments. It reflects on Jamaica’s key role in the Caribbean and in global debates and networks for reparations. Finally, I show the importance of the demands not only for the Caribbean region but also for a necessary confrontation with slavery and colonialism as a common heritage in Europe.